Antibodies in Autoimmune Human Neurological Disease: Pathogenesis and Immunopathology - Williams, Jon P.; Carlson, Noel G.; Greenlee, John E. (Seminars in Neurology, 2018)
Immune-mediated processes represent a rapidly expanding categorical etiology for neurological disease manifestations spanning all subspecialties of neurology. Neural autoantibodies can be grossly divided into two main groups based on localization of the antigen: intracellular and cell membrane/synaptic antibodies. Antibodies reactive with neuronal membrane antigens have been identified in serum and cerebrospinal fluid of patients developing neurological disease either independent of or associated with cancer comorbidity, whereas antibodies directed against intracellular targets have a much higher rate of associated malignancy. Antibodies to neuronal membrane proteins such as the N-methyl-D-aspartate (NMDA) receptor are considered directly pathogenic based on disease models. Similar evidence exists for far fewer autoantibodies directed against intracellular targets. Attempts to produce an antibody-mediated animal model of human paraneoplastic disease have been unsuccessful to date. In this article, we review antineural antibodies and their clinical associations, briefly discuss recently characterized entities, and present proposed mechanisms of antibody pathogenicity.
Keywords: paraneoplastic; autoimmune; encephalitis; antibody; pathogenesis